Human Resource Transformation in Hospitals: The Role of Digital Capabilities, Digital Training, and Organizational Agility - Anita Linda Yohana Pratasik; Irvan Trang; Merinda Pandowo; Genita Lumintang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Digital transformation in healthcare requires hospitals to strengthen human resources that can adapt to technological change. This study aims to analyze the influence of digital capability and digital training on human resource transformation, with organizational agility as a mediating variable, in hospitals in North Sulawesi Province. A quantitative approach with a survey method was employed, involving 200 hospital workers who use digital technology in their work. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The findings show that digital capability has a positive and significant effect on organizational agility (β = 0.400; p < 0.001) and human resource transformation (β = 0.371; p < 0.001). Digital training also positively and significantly affects organizational agility (β = 0.395; p < 0.001) and human resource transformation (β = 0.133; p = 0.010). Organizational agility further contributes positively to human resource transformation (β = 0.374; p < 0.001). Mediation analysis confirms that organizational agility partially mediates the effects of digital capability and digital training on human resource transformation. These findings highlight the importance of integrating digital competence, structured training, and agile organizational systems to support sustainable hospital transformation in line with Dynamic Capability Theory and practical managerial needs.